EXPRESSSION OF SERUM AND SALIVARY MMP-1 AND MMP-9 IN ORAL CANCER, ORAL POTENTIALLY MALIGNANT DISORDERS AND NORMALS. - Baburathinam, Sona; Shyamsundar, Vidyarani; Babu N, Aravindha; Nagarajan, Karthika; Ramshankar, Vijaylakshmi; K, Masthan K.M. (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Matrix metalloproteinases (MMPs) have been implicated in aggressiveness, invasiveness and metastasis of many malignancies including oral squamous cell carcinoma. In the meta-analysis of microarray based Oral Tongue SCC gene expression profiles, MMP-1 and MMP-9 was highly up-regulated .Till date, non-invasive diagnostic aid to detect the malignant potential of OPML or the aggressiveness of OSCC is lacking. With this background we decided to see the level of MMP-1 and MMP- 9 in saliva and serum of OSCC patients with controls. Aim: To determine the level of MMP1 and MMP9 in serum and saliva of patients diagnosed with OSCC, OPML, normal and to correlate with the aggressiveness of the disease. Methodology: The epidemiologic data of the patients reporting to our dental college & Hospital were obtained through an interview. After obtaining written consent from the patient, complete intra oral examination was done, blood, saliva was collected and stored using the standard protocol. ELISA was done on all the samples for MMP-1 and MMP9. Results: MMP-1 in serum and MMP-9 in saliva/ serum was up-regulated in OSCC, moderately up-regulated in OPML when compared to the control group. However MMP-1 in saliva was found to be very low or non detectable. Conclusion: The MMP-9 in saliva/serum and MMP-1 in serum was up-regulated in the OSCC. In future, may be these body fluids can be used to diagnose and to determine aggressiveness of OPML and OSCC by non-invasive techniques. Keywords:Enzyme-Linked Immunosorbent Assay (ELISA ), Matrix Metalloproteinase (MMP),Oral Potentially Malignant Lesions (OPML), Oral Squamous Cell Carcinoma( OSCC), Oral Tongue Squamous Cell Carcinoma ( OTSCC).